How do you solve 7( 2x - 1) = 5( x - 14)?
3 Answers
Explanation:
Expand the brackets
Subtract
Add
Divide both sides by
Explanation:
Distribute and multiply
Then distribute and multiply
Put together, it will look like this
Then add
Then subtract
Divide by
See solution below:
Explanation:
First expand out the brackets:
and
Hence, the equation becomes:
Now rearrange to make
-
Subtract
5x from both sides to obtain:
=> 14x-5x-7=5x-5x-70
=> 9x-7=70 -
Then add 7 to both sides to isolate
x
=> 9x-7+7=-70+7
=> 9x = -63 -
Finally, divide both sides by 9 to obtain
x
=> x=-63/9
Hence,